The Egyptian Financial Supervisory Authority Decision of the Board of Directors of the Authority No. 60 of the Year 2017 Dated 19/4/2017 On Licensing the Companies to Combine Several Financing Activities (Financial Lease, Real Estate Financing, Factoring) and the Controls of Practicing More Than One Activity = الهئية العامة للرقابة المالية قرار مجلس إدارة الهيئة رقم 60 لسنة 2017 بتاريخ 19/4/2017 بشأن الترخيص للشركات بالجمع بين أكثر من نشاط تمويلى (تأجير تمويلى، تمويل عقارى، تخصيم) وضوابط ممارسة أكثر من نشاط - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic